EFFECT OF MINI GAME ON SPEED AND AGILITY OF KHO-KHO PLAYERS - Kakad, Mr. Namdev Ramesh (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The study investigated the effect of mini game on Kho- Kho players as they have problem in speed and agility executing general Kho- Kho skills, with players on, as well as supporting player role in the game situations. The study was an experimental equivalent groups design whereby school level Kho-Kho players (14-17 years) randomly assigned in two groups experimental (n= 15), and control group (n=15). The effectiveness of speed and agility variable was measured by 50 meter dash running, Illinois agility test and game observation instrument. T-test was used to analyze the data, followed with analysis if the test results yielded significant difference. The data clearly shows that obtained T ratio -5.15 was significant at levels 0.05 as the table value 0.00 is less than the calculated T ratios with value the degrees of freedom 28. As p-value<0.05 the difference between effect of mini game on speed and agility was significant.